(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the efficiency of flank laparotomy to obtain intestinal biopsies in horses, as well as the occurrence of complications associated with the procedure. Sixteen healthy adult horses, mixed-breed, four males and 12 females, aged between four and 14 years and mean body weight of 248.40 + 2.28 kg were used. All animals underwent two flank laparotomies for collection of intestinal biopsies, jejunum and large colon, with an interval of 144 hours between collections. Incisional complications were observed in 90% of the animals, including seroma/incisional line infection, and suture line dehiscence. Despite the occurrence of complications, the procedure proved to be easy to perform and suitable for obtaining intestinal biopsies.